Employment, incomes and equality : a strategy for increasing productive employment in Kenya - International Labour Office (Geneva : International Labour Office, 1972)
This is the third major report in three years that the I.L.O. has sponsored on unemployment in a developing country, as part of its contribution to the Second Development Decade. In this report the authors reject the conventional dichotomy of the " dual economy," in which a " modern " sector, with its up-to-date, western technology is the source of all " progress," and the task of development policy is to draw the great majority who (supposedly) work in the " traditional " or " subsistence " sector into the web of " modern " activities. The non-market oriented subsistence household has virtually disappeared in Kenya (and in the rest of Africa as well), and it is time it made its exit from textbooks and journals also. A more illuminating distinction, the authors suggest, is that between the " formal " and " informal " sectors of the economy. The " formal " sector consists mostly of large, foreign-owned and mainly foreign-managed enterprises, which use capital-intensive techniques and pay (in an African context) high wages. By contrast, the " informal " sector, though just as modern (in the sense of being market-oriented, efficiency-conscious and increasingly urban) consists of relatively small and almost wholly indigenous enterprises, which use capital-saving techniques and where average earnings, though typically lower than in the formal sector, are significantly higher than the average small-farm wage.
"Report of an inter-agency team financed by the United Nations Development Programme and organised by the International Labour Office."
Includes bibliographical references.
rpm 03/04/2018
Loans
Keywords: Manpower policy